Respuesta :

Answer:

y = -2x + 4

Step-by-step explanation:

slope intercept form:

y = mx + b

m = slope = -2

b = y-intercept

x = x = 3

y = y = -2

Plug in the corresponding numbers to the corresponding variables:

-2 = (-2) * (3) + b

Simplify. First, multiply:

-2 = (-6) + b

Next, isolate the b. Note the equal sign, what you do to one side, you do to the other. Add 6 to both sides of the equation:

-2 (+6) = -6 (+6) + b

b = -2 + 6

b = 4

Plug in 4 for b in the equation:

y = mx + b

y = -2x + 4

~

ACCESS MORE